Microwave-Assisted Synthesis of Dibenzo-Crown Ethers - Eliseo C. Torrejos, Rey; M. Nisola, Grace; B. Beltran, Arnel; Jun Park, Myoung; R. Patil, Basavaraj; Lee, Seong-Poong; Gil Seo, Jeong; Chung, Wook-Jin (Letters in Organic Chemistry, 2014)
Microwave-assisted organic synthesis (MAOS) for dibenzo-substituted crown ethers is presented. Two routes were developed: (1) one-pot MAOS for symmetric dibenzo-crown ethers (DBC) and (2) a two-step MAOS via diphenol intermediates for both symmetric and asymmetric DBCs. MAOS were carried out in open or closed vessels, with or without temperature control at various microwave settings using different bases and reactants. Open vessel MAOS was limited by the volatility of reactants hence was less preferred than the closed vessel MAOS. DBC formation was highly affected by the cation size of the base, which acted as a template ion during DBCs ring closure. Closed vessel MAOS without temperature control was found most appropriate for DBC synthesis. Symmetric DBCs were conveniently obtained via one-pot MAOS whereas asymmetric DBCs were obtained from two-step MAOS via diphenol intermediates. The method was found expedient as it afforded satisfactory yields at considerably shorter reaction time than those in conventional methods.
Keywords: etherification